The Influence of Mudharabah Financing and Murabahah Financing on Net Profit in Sharia Commercial Banks in Indonesia 2019–2020 - Prasetya, Aulia Dinda; Winarsih, Winarsih (IJIBE (International Journal of Islamic Business Ethics), 2024)
Mudharabah and Murabahah Financing are part of the Sharia Commercial Bank program, which aims to increase net profit. From 2019 to 2020, Mudharabah and Murabahah Financing were included in the three types of financing most popular with customers. The higher the value of Mudharabah and Murabahah Financing, the higher the net profit generated. This research analyzes the influence of Mudharabah and Murabahah Financing on the net profit of Sharia Commercial Banks in 2019–2020. The population of this study is Sharia Commercial Banks registered with the OJK in 2019-2020. The sample was taken using a purposive sampling method, obtaining a sample of 8 Sharia Commercial Banks. This study used secondary data, which uses documentation data collection methods. This study found that Mudharabah Financing variable positively affects the net profit of Sharia Commercial Banks. Meanwhile, Murabahah Financing variable does not affect the net profit of Sharia Commercial Banks.